Sex-Specific Regulation of Gene Expression Networks by Surfactant Protein A (SP-A) Variants in Alveolar Macrophages in Response to Klebsiella pneumoniae - Thorenoor, Nithyananda; Kawasawa, Yuka Imamura; Gandhi, Chintan K.; Floros, Joanna (Frontiers in Immunology, 2020)
Surfactant protein A (SP-A) in addition to its surfactant-related functions interacts with alveolar macrophages (AM), the guardian cells of innate immunity in the lungs, and regulates many of its functions under basal condition and in response to various pressures, such as infection and oxidative stress. The human SP-A locus consists of two functional genes, SFTPA1 and SFTPA2, and one pseudogene. The functional genes encode human SP-A1 and SP-A2 proteins, respectively, and each has been identified with several genetic variants. SP-A variants differ in their ability to regulate lung function mechanics and survival in response to bacterial infection. Here, we investigated the effect of hSP-A variants on the AM gene expression profile in response to Klebsiella pneumoniae infection. We used four humanized transgenic (hTG) mice that each carried SP-A1 (6A2, 6A4) or SP-A2 (1A0, 1A3), and KO. AM gene expression profiling was performed after 6 h post-infection. We found: a) significant sex differences in the expression of AM genes; b) in response to infection, 858 (KO), 196 (6A2), 494 (6A4), 276 (1A0) and 397 (1A3) genes were identified (P < 0.05) and some of these were differentially expressed with ≥ 2 fold, specific to either males or females; c) significant SP-A1 and SP-A2 variant-specific differences in AM gene expression; d) via Ingenuity Pathway Analysis (IPA), key pathways and molecules were identified that had direct interaction with TP53, TNF, and cell cycle signaling nodes; e) of the three pathways (TNF, TP-53, and cell cycle signaling nodes) studied here, all variants except SP-A2 (1A3) female, showed significance for at least 2 of these pathways, and KO male showed significance for all three pathways; f) validation of key molecules exhibited variant-specific significant differences in the expression between sexes. and a similarity in gene expression profile was observed between KO and SP-A1. These results reveal for the first time a large number of biologically relevant functional pathways influenced in a sex-specific manner by SP-A variants in response to infection. These data may assist in studying molecular mechanisms of SP-A-mediated AM gene regulation and potentially identify novel therapeutic targets for K. pneumoniae infection.